Solidification characteristics of die cast a308 aluminium alloy under different vibratory conditions - Yadav, Siddharth (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Solidification characteristics; die cast a308; aluminium alloy; under different vibratory conditions